2013
DOI: 10.1136/bcr-2012-007975
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant amyotrophic lateral sclerosis and paraclinical laboratory features of multiple sclerosis: coincidence or causal relationship?

Abstract: We report a 55-year-old patient, presenting with paresis, muscle atrophy and dysarthria, all symptoms accordable to definite amyotrophic lateral sclerosis (ALS). However, MRI and cerebrospinal fluid show abnormalities typical of multiple sclerosis (MS). On the basis of this case report, we discuss possible overlaps between both diseases by comparing clinical and paraclinical features including laboratory, radiological and electrophysiological diagnostics. As genetic, as well as environmental, factors are assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this study, we have applied several statistical approaches to the investigation of shared susceptibility loci between the neurological diseases MS and ALS, which are both thought to involve inflammatory and neurodegenerative components (1,17,18) and for which case reports and epidemiological studies have reported co-occurrence within individuals or families (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The strength of the study is that different statistical approaches are consistent in demonstrating that the number of regions in the genome with evidence for an overlap in susceptibility between the two diseases is not more than expected by chance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have applied several statistical approaches to the investigation of shared susceptibility loci between the neurological diseases MS and ALS, which are both thought to involve inflammatory and neurodegenerative components (1,17,18) and for which case reports and epidemiological studies have reported co-occurrence within individuals or families (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The strength of the study is that different statistical approaches are consistent in demonstrating that the number of regions in the genome with evidence for an overlap in susceptibility between the two diseases is not more than expected by chance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for diseases classified as neurodegenerative such as ALS, an inflammatory or immune component has been implicated but is not yet conclusive (17,18). Case reports have described patients affected by both diseases (19)(20)(21)(22)(23)(24) and an increased co-occurrence of MS and ALS compared with what is expected has been observed (25,26). Studies also report an increased risk of MS among relatives of patients suffering from ALS and vice versa (27)(28)(29), and some but not all studies report geographical correlation in mortality rates of both diseases (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…It has been described in the literature only in the context of MS, suggesting a potential interaction between neuroinflammation and neurodegeneration. 8 To our knowledge, this is the first case report in the literature to describe both ALS and NMO in a patient.…”
Section: Introductionmentioning
confidence: 74%
“…The coexistence of ALS and an inflammatory demyelinating disease has been described previously only in the context of MS, suggesting that ALS and MS may share patterns of neuroinflammation, specifically signaling pathways and blood–brain barrier disruption. 8 Activated transcription factor nuclear factor kappa-light-chain-enhancer of activated B cells (NK-kB) was found in both oligodendrocytes of active MS plaques and astrocytes, but not motor neurons, of patients with ALS. 9,10 Similar neuroinflammatory mechanisms may exist in NMO pathogenesis.…”
Section: Discussionmentioning
confidence: 99%